Penguatan Literasi Moderasi Beragama Melalui Platform Digital dan Media Sosial di Kalangan Mahasiswa Pergerakan Mahasiswa Islam Indonesia (PMII) Pandeglang - Kosim, Nandang; Royhatudin, Aat; Hidayatullah, Agus (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This research is motivated by the rise of intolerant and radical content on social media which influences students' perceptions of diversity. Apart from that, low digital literacy and the ability to filter information are also factors that worsen this situation. The urgency of this research lies in the high use of social media among students, which makes it one of the most effective tools for spreading the values of religious moderation. However, a lack of awareness and ability to use social media wisely can be a challenge in itself. By strengthening digital literacy and religious moderation, it is hoped that PMII students can become catalysts for more inclusive change in society. This research presents novelty by focusing on digital and social media-based interventions to strengthen religious moderation literacy.                        This research uses a qualitative approach with data collection techniques through in-depth interviews, participant observation, and analysis of related documents. The main respondents were PMII students who were actively involved in religious organization activities in Pandeglang. Data analysis was carried out using a thematic approach to identify patterns and themes related to religious moderation literacy.                                   The results of this research show that there is a fairly good understanding of the principles of moderation, but there are also several challenges and obstacles faced in implementing these values in everyday life. Factors such as environmental influences, social media, and group pressure can influence the understanding and practice of religious moderation. In the context of digital literacy, several studies show that students' digital literacy level is still relatively low, especially in recognizing hoax and intolerant content. It is hoped that the implementation of this research can increase understanding and practice of religious moderation, so that students can become agents of positive change in building an inclusive and harmonious society.